Effects of Tamarillo (Cyphomandra betacea (Cav.) Sendtn.) on body weight, biochemistry, antioxidant enzyme, inflammatory biomarkers, liver and kidney in high fat diet-induced obese rats - Abdul Kadir, Noor Atiqah Aizan (2015)
Obesity has reached an epedimic levels in Malaysia, where the prevalence of overweight and obese adult increased from 29.1% and 14.0% in 2006 to 29.40% and 15.10% in 2011 respectively. This study aims to investigate the beneficial effects of Cyphomandra betacea on body weight, biochemistry, antioxidant enzyme, inflammatory biomarkers,and liver and kidney in adult male Sprague-Dawley rats fed with high fat diet. Rats were fed on either normal chow or high fat diet for 10 weeks for obesity induction and subsequently received tamarillo at low dose (150 mg kg-1) (TLDG), medium dose (200 mg kg-1) (TMDG), high dose (300 mg kg-1) (THDG) or distilled water via oral gavages for another 7 weeks for treatment phase. In this present study, C. betacea treated group showed lower bodyweight and BMI as compared to control positive group.THDG showed lowest bodyweight and BMI followed by TMDG and TLDG. Interestingly, treatment of obese rats with C. betacea led to significant decrement of cholesterol (p<0.05) and significant increment of HDL-c (p<0.05). Positive reduction also can be seen in the triglyceride, LDL-C and also blood glucose. Additionally, there was a positive improvement of superoxide dismutase (SOD) and glutathione peroxidase (GPX) activity along with a significant increase (P<0.05) of total antioxidant status (TAS) in C. betacea treated rats. Further, rats treated with C. betacea show significantly lower in TNF- α and IL-6 (p<0.05). As the liver section of C. betacea treated group were observed, the liver appeared normal with radiating hepatocytes and displayed less fat vacuoles as the dosage increase accordingly. Meanwhile, the kidney histology section of C. betacea treated group showed normal glomerulus, proximal convoluted tubule and distal convoluted tubule. Overall, this study demonstrates the potential use of Cyphomandra betacea for weight maintenance and complimentary therapy to supress some obesity complication sign.